Isoamyl isothiocyanate preserves postharvest quality of matsutake (Tricholoma matsutake) by modulating oxidative and antioxidative homeostasis - Dong, Ruijie; Tian, Wenhuai; ElShamey, Essam; Xiao, Lei; Xiao, Yue; Li, Fadan; Chen, Zhifeng; Ye, Dongmei; Wang, Huayi; Zhu, Tong; Ding, Yumei (Frontiers in Plant Science, 2025)
Water loss, browning, and softening are significant contributors to postharvest economic losses in matsutake. To effectively and safely preserve the quality of matsutake, the optimal concentration of isoamyl isothiocyanate (IAITC) was determined. Matsutake that had just been harvested were put in plastic containers and exposed to IAITC for 15 minutes at 25 ± 2°C, at different concentrations of (0, 10, 30, and 60 μLL-1). And then, the matsutake were stored for 8 days at 5.6 ± 0.6°C and 75 ± 5% relative humidity. Over the course of the storage period, the following parameters were tracked, including changes in firmness, weight loss rate, chitin content, the activities of superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), polyphenol oxidase (PPO), total phenolics and ascorbic acid (ASA). These findings showed that IAITC therapy at a dose of 10 μLL-1 considerably decreased weight loss, increased the activity of antioxidant enzymes, and maintained antioxidant content. Additionally, this treatment inhibited PPO activity, decreased malondialdehyde (MDA) accumulation, and maintained chitin content, thereby ensuring the integrity of the cell membranes. These changes contributed to the preservation of both the sensory and nutritional quality of the matsutake. In conclusion, IAITC treatment primarily enhanced antioxidant activity and reduced oxidative damage, thereby delaying the senescence of matsutake and maintaining their quality. This study provides novel insights into the biological mechanisms underlying postharvest preservation using IAITC and lays the foundation for further research and the promotion of its application in matsutake mushroom postharvest management.